Partnersko zdravljenje partnerskega alkoholizma v terapevtski skupini - Rugelj, Janez (Obzornik zdravstvene nege, 1985)
Primary objectives of the management of alcoholism are to revive emotional life and to establish emotional equilibrium of a married couple. The requisite for successful treatment of alcoholism is a sound relationship between a man and his wife. In cases in which both of them are addicted, the drinking problem is much more difficult to solve; in the course of treatment the alcoholics cannot represent a »healthy environment« to each other. Assistance is to be looked for in a therapeutic group. There they can listen to other group members relating openly their own experiences. The author describes a theoretical basis of the interaction method of evaluating personality transformation of an alcoholic and his/her spouse. The paper is complemented by exhaustive accounts given by a treated couple of alcoholics. The therapist who had monitored the modification of their personalities over a period of 6 years, refers to this change as » ... a deep insight, a deeply moving sincerity and a complete belonging to each other, which constitutes a unique success, the greatest one I have ever seen in my therapeutic practice.«